Systems insight into the spore germination of Streptomyces coelicolor - Strakova, Eva; Bobek, Jan; Zikova, Alice; Rehulka, Pavel; Benada, Oldrich; Rehulkova, Helena; Kofronova, Olga; Vohradsky, Jiri (Journal of proteome research, 2013)
An example of bacterium, which undergoes a complex development, is the genus of Streptomyces whose importance lies in their wide capacity to produce secondary metabolites, including antibiotics. In this work, a proteomic approach was applied to the systems study of germination as a transition from dormancy to the metabolically active stage. The protein expression levels were examined throughout the germination time course, the kinetics of the accumulated and newly synthesized proteins were clustered, and proteins detected in each group were identified. Altogether, 104 2DE gel images at 13 time points, from dormant state until 5.5 h of growth, were analyzed. The mass spectrometry identified proteins were separated into functional groups and their potential roles during germination were further assessed. The results showed that the full competence of spores to effectively undergo active metabolism is derived from the sporulation step, which facilitates the rapid initiation of global protein expression during the first 10 min of cultivation. Within the first hour, the majority of proteins were synthesized. From this stage, the full capability of regulatory mechanisms to respond to environmental cues is presumed. The obtained results might also provide a data source for further investigations of the process of germination.
Keywords: proteom; Gene Expression Regulation, Developmental; 2D gelová elektroforéza; antibakteriální látky; Spores, Bacterial; Protein Biosynthesis; proteosyntéza; spory bakteriální; Streptomyces coelicolor; Electrophoresis, Gel, Two-Dimensional; hmotnostní spektrometrie; Proteome; Anti-Bacterial Agents; vývojová regulace genové exprese; Mass Spectrometry; regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial